Efficient ibuprofen removal using enzymatic activated ZIF-8-PVDF membranes - Ayat Hassan; Shadi W. Hasan; Bart Van der Bruggen; Sulaiman Al-Zuhair (Cleaner Engineering and Technology)
This study investigated the development of poly(vinylidene fluoride) (PVDF) hybrid ultrafiltration membranes, where ZIF-8 nanocrystals are synthesized in situ within the membrane pores. These ZIF-8 embedded membranes are specifically designed for the treatment of emerging pollutants, such as ibuprofen. The optimized membrane, characterized by a higher concentration of ZIF-8 and greater surface coverage, exhibited significantly enhanced performance and improved properties, including increased hydrophobicity and mechanical strength. By increasing the zinc concentration from 0.2 to 0.3 M during the preparation of the ZIF-8 coated membrane, hydrophobicity was enhanced, as indicated by an increase in the contact angle from 60.3° to 87.2°, along with improved porosity from 41.3% to 60.5%. Further performance enhancements were achieved by encapsulating enzymes, specifically laccase and peroxidase, within the ZIF-8 coated membrane. A comparison of ibuprofen removal by these enzymes showed that peroxidase was slightly more effective, reaching a maximum removal efficiency of approximately 45% within 2 h. The biocatalytic membranes demonstrated a high stability and reusability, underscoring their potential for efficient ibuprofen removal. These findings highlight the efficacy of ZIF-8-coated PVDF membranes as advanced tools for water purification, offering significant improvements in both purification efficiency and membrane stability.